Community Preparedness Level in the Area Nurul Haq Shelter Against the Threat of Earthquake and Tsunami Disasters - Ashar, Faisal; Pratama, Putra Jonita (CIVED, 2023)
The city of Padang is an area that is prone to earthquakes that have the potential to cause tsunamis. This can be seen from historical data on earthquakes in Padang City. There is a prediction of a large-scale earthquake caused by the Mentawai megathrust fault, where the city of Padang is predicted to be affected by the earthquake and tsunami. Parupuk Tabing is included in the red area if a tsunami disaster occurs. Parupuk Tabing has a shelter to reduce the impact if an earthquake and tsunami disaster occurs. One of them is the Nurul Haq Shelter. Currently, the population around the shelter is around 4,000 people, but the level of preparedness for the dangers of earthquakes and tsunamis is not yet known. This research uses parameters compiled by LIPI – UNESCO 2006, where the parameters tested are; knowledge about earthquake and tsunami disasters, emergency response plans, early warning systems, and resource mobilization. Based on the results of data analysis and research discussions, it was concluded that the level of community preparedness in facing earthquake and tsunami disasters in the area around the Nurul Haq Shelter was included in the very prepared category, namely with an index of 80.97. Then, the knowledge and attitude parameters have a score of 84.78 or "Very Ready", and for the emergency response plan parameters they get a score of 76.57 or "Ready", and for the disaster warning parameters they get a score of 78.36 or "Ready", finally, for the resource mobilization parameter, it got a score of 80.97 "Very Ready". In general, the conclusion is that the community around the shelter understands and is ready to face the threat of earthquakes and tsunamis.